Phormium tenax—a proving - McIvor, E.G. (British Homeopathic Journal, 1980)
Though numerous symptoms were experienced, as detailed above, four special effects were particularly noted throughout the proving.1. With the exception of the left hand and left knee, all sensations were mainly confined to the right side—right hand, right wrist, right forearm, right elbow, right knee, right ankle, right side of pelvis, right side of the abdomen. Phormium tenax appears to be a right-sided remedy, with the exceptions that both knees were involved equally and the symptoms of the left fingers were worse than those of the right fingers.2. Despite the physical symptoms, there was a strong feeling of well-being. Sleep was deep, refreshing, and undisturbed. The day's work was accomplished with less fatigue. The symptoms were > mentally, < physically.3. Phormium tenax is a rheumatic remedy, mainly a remedy suitable for joint afflictions. The sensations of puffiness of the joints, weakness in the joints, and the symptom < on pressure suggest inflammation of the synovial linings of the joints. This remedy would appear to suit rheumatoid arthritis in preference to osteo-arthritis.The pains were mainly drawing, stitching pains. On pressure the joints also felt bruised and sore with some aching. There were also sharp needle like pains, and some twitching of the muscles. All pains were < cold, dry, fine weather, > warm wet weather, < 4 a.m. to 11 a.m., < resting in bed or sitting, i.e. < resting, > continued motion. Sometimes < movement to begin with, though ultimately always > with motion. < pressure. e.g. applied pressure on standing (pressure from weight of body).The primary effects were on the fingers of both hands, especially the left hand, the right wrist, right ankle and right heel, and both knee joints. Involvement of the right elbow was also noted to a lesser degree.4. Phormium tenax appears to be a strong diuretic. Urine output was markedly increased. The urine was dark yellow or greenish-yellow and had a strong through normal odour. It appeared to be very much more concentrated than usual.